Circulating Cytokine Profiles and Their Relationships with Autoantibodies, Acute Phase Reactants, and Disease Activity in Patients with Rheumatoid Arthritis. (2nd January 2011) - Meyer, Pieter W. A.; Hodkinson, Bridget; Ally, Mahmood; Musenge, Eustasius; Wadee, Ahmed A.; Fickl, Heidi; Tikly, Mohammed; Anderson, Ronald
Abstract : Our objective was to analyse the relationship between circulating cytokines, autoantibodies, acute phase reactants, and disease activity in DMARDs-naïve rheumatoid arthritis (RA) patients (n = 140 ). All cytokines were significantly higher in the RA cohort than in healthy controls. Moderate-to-strong positive intercorrelations were observed between Th1/Th2/macrophage/fibroblast-derived cytokines. RF correlated significantly with IL-1 β, IL-2, IL-4, IL-10, IL-12, G-CSF, GM-CSF, IFN- γ, and TNF (P < .0001 ), and aCCP and aMCV with IL-1 β, IL-2, IL-4, and IL-10 (P < .0002 ), while IL-6 correlated best with the acute phase reactants, CRP, and SAA (P < .0001 ). In patients with a DAS28 score of ≥5.1, IFN- γ, IL-1 β, IL-1Ra, TNF, GM-CSF, and VEGF were significantly correlated (P < .04 – .001 ) with high disease activity (HDA). Circulating cytokines in RA reflect a multifaceted increase in immune reactivity encompassing Th1 and Th2 cells, monocytes/macrophages, and synovial fibroblasts, underscored by strong correlations between these cytokines, as well as their relationships with RF, aCCP, and aMCV, with some cytokines showing promise as biomarkers of HDA.